(untitled) (Journal of actual problems of jurisprudence, 2019)
The author carried out the analysis of the procedural status and function of bodies of supervision in modern criminal legal proceedings of the Kyrgyz Republic, in particular public prosecutor’s supervision of legality in criminal procedure activity of the investigation authorities, promoting providing guarantees of legality at investigation of crimes Кеуwords: attorney, criminal procedure, the functions of the state, a consequence of the law.